Evaluation of Collaborative Governance in Realizing Bureaucratic Reform through Smart City Implementation in Cimahi City - Zaenal Abidin AS Abidin AS; Titin Rohayatin (Department of Public Administration, 2025)
Collaborative governance involves public institutions engaging non-state stakeholders in consensus-oriented, deliberative decision-making for public policy. In Cimahi City, stakeholder involvement in bureaucratic reform through the Smart City initiative is vital, yet collaboration remains underdeveloped. This study aims to describe, analyze, and map the roles, challenges, and efforts of Pentahelix actors government, private sector, academia, media, and civil society in implementing the Smart City concept. Using a descriptive-analytical method with a qualitative approach, the research explores collaboration through communication, coordination, and cooperation. Findings show the government is responsible for regulations, procurement, education, and assistance but is perceived as ineffective. The private sector aids job creation, yet opportunities remain limited. Higher education contributes innovation and expertise in policymaking. Media disseminates information and fosters networks. Public participation is low, especially in idea-sharing and technology use. NGOs assist through training and empowerment programs. Key barriers include weak communication, lack of coordination, and differing stakeholder perspectives. To address these issues, the government established a Smart City Expert Council as a collaborative platform. Overall, while roles are defined, actual implementation faces structural and relational challenges, requiring stronger integration and mutual understanding among all Pentahelix pillars to drive effective bureaucratic reform.